Do new opportunities arise for women in post-war countries? The case of Rwanda - Kati Schindler (Weekly Report, 2011)
Violent conflict is a severe obstacle for economic development and poverty alleviation. It harms humans and destroys physical property. However, conflict may also trigger social change. This contribution discusses how women may assume new economic responsibilities in a post-conflict environment. The analysis focuses on the case of Rwanda, a small landlocked nation in Central Africa that erupted into genocide in 1994. During the genocide, more men than women died, which caused a shortage of men in the post-genocide period. It is shown that the genocide affected women in different ways. Many widows became breadwinners of their household and took on new economic activities. In contrast, both wives and unmarried women conform to the traditional female gender ideal. This may be a strategy to improve their chances of getting married.
Keywords: J12; J22; O12; 330; gender roles; Rwanda; time allocation; violent conflict